Asiatic Acid, a Natural Compound that Exerts Beneficial Effects on the Cystometric and Biochemical Parameters in the Retinyl Acetate-Induced Model of Detrusor Overactivity - Andrzej Wróbel; Anna Serefko; Aleksandra Szopa; Ewa Poleszak (Frontiers Media S.A., 2021)
Scientists have been constantly looking for new synthetic and natural compounds that could have beneficial effects in bladder overactivity. Our attention was drawn by asiatic acid that influences a number of molecules and signaling pathways relevant for the proper functioning of the urinary tracts in humans. In the present project we wanted to check whether asiatic acid would have positive effects in the confirmed animal model of detrusor overactivity (DO) and whether it would affect the bladder blood flow, urothelium thickness, inflammatory and oxidative stress markers, neurotrophic and growth factors, and other parameters important for the activity of the urinary bladder. The outcomes of our study showed that a 14-day administration of asiatic acid (30 mg/kg/day) by oral gavage normalizes the cystometric parameters corresponding to DO and reduces the accompanying oxidative stress (measured by the levels of malondialdehyde-61,344 ± 24,908 pg/ml vs. 33,668 ± 5,071 pg/ml, 3-nitrotyrosine-64,615 ± 25,433 pg/ml vs. 6,563 ± 1,736 pg/ml, and NOS2-2,506 ± 411.7 vs. 3,824 ± 470.1 pg/ml). Moreover, it decreases the urinary secretion of neurotrophins (BDNF-304.4 ± 33.21 pg/ml vs. 119.3 ± 11.49 pg/ml and NGF-205.5 ± 18.50 vs. 109.7 ± 15.94 pg/ml) and prevents the changes in a range of biomarkers indicating the dysfunction of the urinary bladder, CGRP (421.1 ± 56.64 vs. 108.1 ± 11.73 pg/ml), E-Cadherin (773.5 ± 177.5 pg/ml vs. 1,560 ± 154.5 pg/ml), OCT3 (3,943 ± 814.6 vs. 1,018 ± 97.07 pg/ml), SNAP-23 (6,763 ± 808.9 pg/ml vs. 3,455 ± 554.5 pg/ml), SNAP-25 (2,038 ± 162.7 pg/ml vs. 833.3 ± 65.48), substance P (171.7 ± 16.86 pg/ml vs. 65.07 ± 8.250 pg/ml), SV2A (1,927 ± 175.3 pg/ml vs. 1,154 ± 254.9 pg/ml), tight junction protein 1 (360.1 ± 95.05 pg/ml vs. 563.4 ± 65.43 pg/ml), VAChT (16,470 ± 2,419 pg/ml vs. 7,072 ± 1,339 pg/ml), VEGFA (318.3 ± 37.89 pg/ml vs. 201.5 ± 22.91 pg/ml). The mentioned parameters are associated with smooth muscle contractions, urothelial barrier, transportation and release of transmitters, or bladder compensation. Thus, the presented findings allow to suggest a possible future role of asiatic acid in the prevention of conditions accompanied by DO, such as overactive bladder.